2019
DOI: 10.1177/0333102419848121
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cranial nerve blocks for the transitional treatment of chronic headaches

Abstract: Background Multiple cranial nerve blocks of the greater and lesser occipital, supraorbital, supratrochlear and auriculotemporal nerves are widely used in the treatment of primary headaches. We present efficacy and safety data for these procedures. Methods In an uncontrolled open-label prospective study, 119 patients with chronic cluster headache, chronic migraine, short lasting unilateral neuralgiform attack disorders, new daily persistent headaches, hemicrania continua and chronic paroxysmal hemicrania were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
0
23
0
3
Order By: Relevance
“…Out of 124 headache patients who had MCNBs in the headache service within the study time period, patients without chronic migraine headache diagnoses were excluded, including those with episodic migraine, 9 cluster headache, 10 occipital neuralgia, 13 paroxysmal hemicranias, 6 cervicogenic headache, 6 and other cranial neuralgias 8 . Outcomes for 64 patients with a diagnosis of chronic migraine who underwent at least 1 MCNB procedure were collected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of 124 headache patients who had MCNBs in the headache service within the study time period, patients without chronic migraine headache diagnoses were excluded, including those with episodic migraine, 9 cluster headache, 10 occipital neuralgia, 13 paroxysmal hemicranias, 6 cervicogenic headache, 6 and other cranial neuralgias 8 . Outcomes for 64 patients with a diagnosis of chronic migraine who underwent at least 1 MCNB procedure were collected.…”
Section: Resultsmentioning
confidence: 99%
“…There have been a few open label series, and more recently randomized control trials on the use of GON blocks in migraine, both with and without steroids 3‐7 . The use of corticosteroids in GON blocks is controversial but some experts argue in favor of it, as it may confer a prolonged antinociceptive effect 3‐4,8 . Unlike GON blocks, multiple cranial nerve blocks (MCNBs) include injecting superficial branches of the trigeminal nerve as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, nine patients with palpation tenderness over the greater occipital nerve, superior orbital nerve, or trochlear area were treated with one or more blockades to the tender areas, and complete pain relief was found in five patients and partial relief in four patients. Finally, a larger series including six HC patients, who all had failed GONB, found a good response to MCNB in five patients [57]. Pooled analyses of two studies [23,26] with a total of 30 participants showed a responder proportion on GONB of 0.23 (95% CI 0.09 to 0.41), while pooled analyses of two studies [23,28] with a total of 13 participants showed a responder proportion on SONB of 0.83 (95% CI 0.55 to 1.00).…”
Section: Nerve Blockadesmentioning
confidence: 87%
“…The long-term benefit and low rate of side effects, mostly mild and localized [66], make GON blocks a relevant option to be considered in the early treatment of cluster bouts [67]. There is limited evidence for the application of multiple cranial nerve injections [68] and a higher morbidity in comparison with a single injection.…”
Section: Local Corticosteroidsmentioning
confidence: 99%